Sosialisasi Dan Pemanfaatan Aplikasi Belajar TK Dan PAUD Berbasis Smartphone Android Di Lingkungan RT. 04/01 Kp. Berkat Kalisuren - Muhamad Irsan; Forkas T.S.B; Ahmad Husain (Jurnal Informasi Pengabdian Masyarakat, 2023)
The development of information and communication technology provides convenience in accessing information, including interacting with the social environment through social media as well as in terms of utilizing this technology to increase knowledge. Socialization and Utilization of Android Based Kindergarten and PAUD Learning Applications at PKK in RT.04/01 Kp. Thanks to Kalisuren, it aims to add to maximizing the usability of an android smartphone that offers many interesting features so as to provide more value to the knowledge of both parents and children. This application contains so many choices in the electronic learning process so that you stay focused. parental guidance is needed in order to be able to supervise and also provide an explanation of the discussion material in the application. Responding to advances in information technology provides encouragement and motivation for our team to carry out community service in the hope of optimizing the use of information technology in various opportunities and activities.